Fredholm Integral Equations with Degenerate Kernel Method in Two Dimensional (Faculty of Education Scientific Journal, 2024)
In this paper, The existence and uniqueness of solution is studied in L2[a,b]× L2[c,d]. Moreover, we use a degenerate kernel method to transform the integral equation into a linear algebraic system. In addition, the existence and uniqueness of this linear algebraic is discussed. Finally, numerical examples are considered and the error, in each case is computed by Maple.
Keywords: Fredholm Integral Equation; The existence and uniqueness solution; Degenerate kernel method